COLLABORATIVE LEARNING TO FOSTER STUDENT’S CREATIVITY IN ELEMENTARY SCHOOL LEVEL - Anggriawan, Tommy; Fahmi, Yahya; Muzaqi, Ajie Hanif (UPT. PKM UB, 2023)
In a dynamic culture of modern society, the trend of collaboration has been developed into various models and implementation. It has become of essential skills that needs to be owned by individual in real social life scenario. A collaborative learning (CL) is one of well-known method that is trusted as viable way to train collaborative practice among pupils in recent years. However, the education concept of CL is a genuine and has no fixed structure, therefore the research to elaborate them in various aspect is important. This research aims to explore the implementation of CL that conducted through community service program carried out by administrative science student of Brawijaya University to the elementary student of Bocek III in Malang Regency, Indonesia. It applies a participatory research appraisal that require constant participation of researcher along the progress of the research. The result of this research highlights two primary information, first the CL is applicable method for elementary students, and second the teacher as part of CL program should be aware of behavioral change of elementary students during the program such as politeness or maturity level.